Analisis Kualitas Produk dalam Keputusan Pembelian Batik pada UKM An Nisa di Kota Jambi - Pupu Sopini (J-MAS (Jurnal Manajemen dan Sains), 2019)
The research aims to analyse and describe the quality of batik products based on the assumptions and opinions of batik consumers in their purchasing decisions. The type of research used is a qualitative descriptive approach. The population of this research is the number of consumers of Batik An Nisa who use Batik products in 2018. While the sample withdrawal using Slovin formula with 10% precision, the sample obtained as many as 57 people with the technique of random sampling. Method of collecting data using questionnaires. The results showed that from the 7 indicators in variable product quality, the product conformity indicator is on the sub-indicator of the material used good quality shows the score of 198 which is the highest score compared to 6 indicators Other. This is very related to the target market of  Batik An Nisa, where the average purchase of the product is a civil servant (PNS) with an income range of 2–3 million rupiah per month. While the lowest score of 156 is obtained on the product feature indicators a diverse pattern of motive sub can affect the quality of the product, with the results quite agreed. This gives the meaning that more motifs are certainly more and more choices of consumers to buy batik in An Nisa UKM, so that the batik become valuable for consumers.